Pelaksanaan PerKPU No 20 Tahun 2023 dalam Pemasangan Baliho Kampanye - Hamdani, Rahmat; Ikram, Zakiy Meisesa; Ilham, Arifin; Prakasa , Ragil Surya (Jurnal Jejak Hukum Indonesia (JHI), 2024)
Campaigning is one of the stages of holding elections. According to Article 1 point 35 of the Election Law, an election campaign is an election campaign carried out by election participants whose aim is to persuade voters by conveying the election vision, mission, plans and/or self-image and campaign activities conveyed by election participants. Regulated in article 280 paragraph (1) of the Election Law and PerKPU No. 20 of 2023. Article 70 paragraph (1) and Article 72A of PerKPU 20/2023 regulate prohibitions on election campaigning, regarding prohibitions carried out by implementers, participants and election campaign teams.